Moral Integration and Transparency as Cornerstone of Safety in Chemistry Laboratories - H. Al-Dahhan, Wedad; Abd Ali, Ali; E. Rodda, Kabrena; F. Alkaim, Ayad; H. Hussein, Falah; Yousif, Emad (International Journal of Psychosocial Rehabilitation, 2020)
Society benefits when chemists work to raise public awareness by adopting high ethical standards, working to reach out to and assist the community around them, and fostering innovation and teamwork in their research and associated collaborations. When chemists devote their efforts to benefitting mankind and protecting the environment for future generations, people’s trust in science and scientists grows. In recognition of this, from 2014 to 2016, the American Chemical Society (ACS), supported by Pacific Northwest National Laboratory (PNNL), led a U.S. Department of State-funded project to develop a Global Chemists’ Code of Ethics. In this regard, transparency, integrity, and moral responsibility form the basis for ethical behavior in all scientific endeavors, including laboratory safety, presenting data, publishing, and protecting the environment. Unfortunately, while society has an interest in promoting ethical behavior in its scientific community, learning institutions and chemical enterprises may minimize training and education programs on chemical ethics. Rodda et al. have previously emphasized the importance of robust scenario-based training that provides low-risk opportunities to practice ethical behavior to strengthen people’s resolve to act when bigger ethical problems arise. In this manuscript, we present a straightforward roadmap to promote transparency as a means to bolster ethical behaviors of people and amenities. This roadmap, if implemented appropriately, could assist not only in maintaining research transparency and integrity but also in avoiding or minimizing the effects of dangerous laboratory accidents.